EXTERNAL INFLUENCES AND SUPPORTS TO PESANTREN’S SOCIO-ECONOMIC ACTIVISM IN THE CHANGING CONTEXT - Isbah, M. Falik (Shirkah: Journal of Economics and Business, 2019)
This article aims to provide a context for discussions on pesantren?s socio-economic projects in contemporary Indonesia. It highlights current programs and engagements of agencies with pesantren in facilitating and supporting them to carry out socio-economic projects. In doing so, it will discuss the current programs of Nahdlatul Ulama (NU), particularly its organisational arms RMI (Rabitah Ma'ahid al Islamiyah, Association of Islamic Pesantren) and Lakpesdam (Lembaga Pengembangan Sumberdaya Manusia, Institute for Human Resource Development) which support the socio-economic role of pesantren. Then, the article will provide an overview of NGO?s programs in partnership with pesantren. The following section discusses examples of technical and financial support to pesantren from organisations promoting Islamic microfinance. The last section assesses government?s economic projects involving pesantren as to what extent they have affected pesantren?s community engagement. I argue that those external factors have not significantly strengthened pesantren?s capacity to carry out their socio-economic projects. This argument is built on my attempt to assess the extent to which these organisations have contributed to the strengthening of the capacity of pesantren to manage socio-economic projects for their communities.    Keywords: pesantren, socio-economic activism, external supports, NGOs, Nahdlatul Ulama